Direct pentaplex PCR assay: An adjunct panel for meat species identification in Asian food products. (15th January 2019) - Thanakiatkrai, Phuvadol; Dechnakarin, Jirapa; Ngasaman, Ruttayaporn; Kitpipit, Thitika
Highlights: A direct pentaplex PCR assay was developed for identification of meat from dog, duck, buffalo meat, goat, and lamb/mutton. The assay was reproducible, specific, sensitive, and robust for use in real-world food and food products. Of 117 commercial samples, 26 were found to contain unlisted meat species. Abstract: A direct pentaplex PCR assay was developed for the identification of meat from sources other than those declared on the packaging. Species-specific primers were designed, based on the mitochondrial cytochrome oxidase I (COI) gene. The assay amplified specific DNA fragments from dog (230 bp), duck (283 bp), buffalo (363 bp), goat (396 bp), and sheep (477 bp). The proposed method is capable of identifying target species accurately and is reproducible, sensitive and robust for use with real-world foods and food products. In total, 26 of 117 meat and commercial food products tested were shown to contain DNA from species not declared on the label.